Cognitive Skills, Schooling Attainment, and Schooling Resources: What Drives Economic Growth? (2009)
This paper presents evidence that students’ test scores at ages 9 to 15 are not a good proxy for a nation’s stock of human capital. Across countries test scores rise with increases in human capital up to $40,000/adult (2000$), but then decline as human capital increases up to $125,000/adult. Schooling attainment is a better proxy for the human capital stock than test scores, but it is not very useful for statistical analysis because it is not a precise measure. The nation’s stock of human capital, calculated from cumulative investment in schooling, is the schooling measure most correlated with national income.